Tingkat Pengetahuan Peserta Didik Mengenai Makanan Bergizi di SDN Teluk Dalam 3 - Fikri, Muhammad; Basuki, Sunarno; Nurdiansyah (SPRINTER: Jurnal Ilmu Olahraga, 2025)
This study focuses on measuring the level of knowledge of fourth grade students of SDN Teluk Dalam 3 about nutritious food. The background of this study is based on the importance of nutrition education from an early age to prevent nutritional problems such as stunting, especially in the South Kalimantan region which still shows a high prevalence of stunting.  This study used a survey method with a quantitative approach. The instrument used was a questionnaire modified from the General Nutrition Knowledge Questionnaire (GNKQ) and adjusted to the level of understanding of elementary school children. The research sample was all 75 respondents of grade IV students. The results of the study showed that 36% of students had a level of knowledge in the Good category, 33% in the Moderate category, 19% in the Low category, 9% in the Very Good category, and 3% in the Very Low category. These findings indicate that although most students have quite good knowledge, there are still groups that need further educational intervention. The conclusion of this study is the importance of integrating nutrition materials into learning in elementary schools as a preventive step in improving nutritional literacy and children's health from an early age.